2009 Italian cadet national team competition match analysis: technical and tactical study - Dalponte, T. (2011)
1.The most frequent Nage-waza techniques are Sutemi-waza (M= 31.4%; F= 32.4%), followed by Ashi-waza both for males (22.5%) and for females (16.1%). Regarding Ne-waza, we can note the dominance of Shime-waza both for male than for female (M=3.1%; ; F= 7.8%). It is important to underline that female use with more frequency the ground fight than male (M=13; F=37); 2.The most efficacious techniques are, for Nage-waza, Gaeshi-waza (30.8 %), followed by Te-waza ushiro (13.3 %) and Sutemi-waza (11.7 %). Concerning Ne-waza they are Osae-waza (55.6 %); 3.The major number of techniques were executed to the right side, in particular the most frequent techniques to mae-right side and the less frequent to the ushiro-left side.